CTD-O2WMED: Quality controlled dataset of CTD dissolved oxygen profiles in the Western Mediterranean Sea (2004-2023) from R/V oceanographic cruises - Malek Belgacem; Katrin Schroeder; Siv K Lauvset; Marta Álvarez; Jacopo Chiggiato; Mireno Borghini; Carolina Cantoni; Tiziana Ciuffardi; Stefania Sparnocchia (PANGAEA, 2025)
A new dataset from oceanographic cruises in the Western Mediterranean Sea (WMED) was compiled to integrate the previously published regional data product about dissolved inorganic nutrients (CNR-DIN-WMED, Belgacem et al., 2019, 2020). The Mediterranean region is experiencing rapid changes, necessitating high-quality and reliable datasets. However, the scarcity of in-situ observations hinders the understanding of these changes and their impact on biogeochemical cycles. Dissolved oxygen (O2) is a vital component of marine ecosystems and plays a fundamental role in governing nutrient and carbon cycles, underscoring the need for accurate and reliable data. To address this, a high resolution, regional-scale data product was developed to understand decadal variability and spatial/temporal patterns of the ventilation process in the WMED. CTD-Oxygen in the Western Mediterranean Sea (CTD-O2WMED) CNR dataset presents an extensive collection of unpublished oxygen measurements collected between 2004 and 2023, along with a description of the quality assurance procedures. The quality assurance process involves rigorous primary quality control, including sensor post-calibration validation against discrete Winkler titrations, initial screening, and standardization. CTD-O2WMED-original version represents dataset that has passed first-level quality checks, but has not yet been corrected through crossover analysis (i.e., secondary quality control) (Belgacem et al., in review, 2024). The adjusted version of the dataset CTD-O2WMED-adjusted builds upon the original dataset by incorporating the secondary quality control corrections, including inter-cruise crossover analysis using deep reference datasets. The adjusted CTD-O2WMED datasets provide a valuable foundation for investigating long-term changes in dissolved oxygen in the WMED, supporting efforts to track deoxygenation trends, assess ventilation dynamics, and calibrate biogeochemical Argo floats (BGC-Argo), as well as validate regional biogeochemical models.